Tissue engineering strategies applied in the regeneration of the human intervertebral disc - Correia, Joana Correia (2013)
Low back pain (LBP) is one of the most common painful conditions that lead to work absenteeism, medical visits, and hospitalization. The majority of cases showing signs of LBP are due to age-related degenerative changes in the intervertebral disc (IVD), which are, in fact, associated with multiple spine pathologies. Traditional and more conservative procedures/clinical approaches only treat the symptoms of disease and not the underlying pathology, thus limiting their longterm efficiency. In the last few years, research and development of new approaches aiming to substitute the nucleus pulposus and annulus fibrosus tissue and stimulate its regeneration has been conducted. Regeneration of the damaged IVD using tissue engineering strategies appears particularly promising in pre-clinical studies. Meanwhile, surgical techniques must be adapted to this new approach in order to be as minimally invasive as possible, reducing recovering time and side effects associated to traditional surgeries. In this review, the current knowledge on IVD, its associated pathologies and current surgical procedures are summarized. Furthermore, it also provides a succinct and up-to-date overview on regenerative medicine research, especially on the newest tissue engineering strategies for IVD regeneration